Identification of T-cell epitopes in African swine fever virus CD2v and C-type lectin proteins. (10th January 2019) - Burmakina, Galina; Malogolovkin, Alexander; Tulman, Edan R.; Xu, Weidong; Delhon, Gustavo; Kolbasov, Denis; Rock, Daniel L.
Abstract : African swine fever (ASF) is an emerging disease threat for the swine industry worldwide. No ASF vaccine is available, and progress is hindered by lack of knowledge concerning the extent of ASF virus (ASFV) strain diversity and the viral antigens conferring type-specific protective immunity in pigs. Previously, we demonstrated that ASFV serotype-specific proteins CD2v (EP402R) and/or C-type lectin (EP153R) are important for protection against homologous ASF infection. Here, we identified six discrete T-cell epitope regions present on CD2v and C-type lectin using IFN-γ ELISpot assay and PBMCs from ASF immune animals, indicating cellular reactivity to these proteins in the context of ASFV infection and protective immunity. Notably, three of the epitope regions map to previously described serotype-specific signature regions of these proteins. Improved understanding of ASFV protective antigens, relevant epitopes and their diversity in nature will facilitate ASFV subunit vaccine design and development.